Preparation method of pre-lithiated composite carbon material and negative pole piece, and secondary battery

By using prelithiated composite carbon materials in the negative electrode material of lithium-ion batteries, lithium powder is exposed using the dissolution mechanism of the electrolyte layer, the capacity loss problem caused by lithium-ion batteries during volume expansion is solved, and efficient lithium source utilization and battery performance improvement is achieved.

CN119920876APending Publication Date: 2025-05-02DONGGUAN CHAM BATTERY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411922462.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The negative electrode material of existing lithium-ion batteries leads to the reduction and decomposition reaction of electrolyte during volume expansion, resulting in first capacity loss and low circulation capacity. The lithium source utilization rate of pre-lithiation method is low, resulting in poor battery performance.

Method used

Prelithiated composite carbon material is used to improve the first Column efficiency and cycling performance of the battery by filling lithium powder in the carbon matrix and covering the electrolyte layer.

Benefits of technology

It effectively improves the first Coulomb efficiency and circulation performance of lithium-ion batteries, improves the rate performance, and significantly improves the utilization rate of lithium sources, reducing the generation of "dead lithium".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920876A_ABST
    Figure CN119920876A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a pre-lithiated composite carbon material and a negative pole piece, and a secondary battery. The pre-lithiated composite carbon material comprises a carbon matrix, lithium powder and an electrolyte layer coating the carbon matrix. The carbon matrix is a carbon ball comprising a plurality of cavities, the plurality of cavities are sequentially enclosed from inside to outside, the lithium powder is filled in the cavities, and the electrolyte layer can be dissolved in an organic solvent. According to the technical scheme, the carbon matrix is coated with the electrolyte layer, and the cavity of the carbon matrix is filled with the lithium powder. And after the battery is formed, the electrolyte layer is dissolved in the organic solvent of the electrolyte so as to expose the internal lithium powder, and the lithium powder starts to play a role to supplement lithium ions, so that the first coulombic efficiency and the cycle performance of the battery are effectively improved. And the carbon balls serving as the carrier can improve the conductivity of the pole piece and reduce the temperature rise so as to improve the rate capability. The electrolyte in the electrolyte layer dissolved in the organic solvent can improve the electrochemical performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the synthesis of materials for the new energy industry, in particular to the synthesis of a negative electrode material, and more particularly to a preparation method of a pre-lithiation composite carbon material and a negative electrode sheet, and a secondary battery. Background Art

[0002] At present, in order to match the high energy performance requirements of new electronic devices, it is necessary to develop lithium-ion battery technology with high capacity and high energy density. Compared with the new generation of lithium-sulfur and lithium-air battery systems, replacing traditional graphite with silicon or hard carbon composites to break through the current battery capacity limitations is a technical route that can be industrialized in the short and medium term. However, similar high-capacity negative electrode materials often face a sharp problem, that is, under the large volume expansion effect, the reduction and decomposition reaction of the electrolyte at the negative electrode interface will lead to a higher first capacity loss, which is specifically manifested as a decrease in the first coulomb efficiency (silicon-based negative electrode is less than 80%). Since the positive electrode is regarded as a lithium ion storage reservoir in lithium-ion batteries, the first irreversible capacity phenomenon caused by the negative electrode will inevitably cause the actual cycle capacity of the battery to be far lower than the theoretical calculated value.

[0003] Lithium replenishment (also called pre-lithiation) is a method of storing lithium in the electrode in advance to compensate for the initial capacity loss of the battery. It can effectively solve the above-mentioned problem of low initial coulombic efficiency and improve the capacity and cycle stability of the battery.

[0004] So far, the industry has developed a variety of pre-lithiation methods, such as external electrochemical pre-lithiation, chemical pre-lithiation, lithium salt-assisted pre-lithiation, etc. Among them, the one with the greatest potential for industrial development is contact pre-lithiation, that is, the internal short-circuit micro-corrosion reaction that occurs after a metal lithium source is added to the negative electrode and placed in an electrolyte. However, the metal lithium source cannot fully participate in the pre-lithiation reaction process. During the lithium replenishment process, the collapse of the electronic pathway, that is, the direct contact site between the lithium film and the negative electrode, can easily induce the blockage of the internal short-circuit electrochemical loop, causing the pre-lithiation process to end prematurely, which inevitably leads to low lithium source utilization in terms of mechanism. The utilization rate of the lithium source is often less than 65%. There is no doubt that the remaining unconverted lithium source has lost its electronic conductivity and is regarded as a kind of "dead lithium". It gathers at the negative electrode interface to hinder the diffusion and mass transfer of lithium ions, resulting in increased polarization of the battery and lithium precipitation. Pressing a lithium sheet on the electrode will cause the direct contact point between the lithium film and the negative electrode to collapse in subsequent cycles, and the lithium source utilization rate will decrease in the later stages of the cycle, which is not conducive to the continuous lithium replenishment required for long-term cycles. Therefore, the current pre-lithiation method is not perfect. Summary of the invention

[0005] Based on the above problems, the purpose of the present invention is to provide a method for preparing a pre-lithiation composite carbon material and a negative electrode plate, and a secondary battery. This pre-lithiation composite carbon material can not only replenish lithium during use, effectively improving the battery's first coulombic efficiency and cycle performance, but also improve the rate performance.

[0006] To achieve the above-mentioned objectives, the first aspect of the present invention provides a pre-lithiation composite carbon material, comprising a carbon matrix, lithium powder and an electrolyte layer coating the carbon matrix, wherein the carbon matrix is ​​a carbon sphere comprising a plurality of cavities, the plurality of cavities are sequentially arranged from the inside to the outside, the lithium powder is filled in the cavities, and the electrolyte layer is soluble in an organic solvent.

[0007] In the technical solution adopted by the present invention, the electrolyte layer covers the carbon matrix, and the lithium powder is filled in the cavity of the carbon matrix. After the battery is formed, the electrolyte layer dissolves in the organic solvent of the electrolyte to expose the internal lithium powder, and the lithium powder begins to play a role in replenishing lithium ions, thereby effectively improving the first coulomb efficiency and cycle performance of the battery. The carbon ball as a carrier can improve the conductivity of the pole piece, reduce the temperature rise, and improve the rate performance. The electrolyte in the electrolyte layer dissolved in the organic solvent can improve the electrochemical performance of the battery.

[0008] As a technical solution of the present invention, the number of the cavities is 1 to 3.

[0009] As a technical solution of the present invention, the thickness of the electrolyte layer is 10 to 70 nm.

[0010] As a technical solution of the present invention, the electrolyte in the electrolyte layer is at least one of lithium difluorooxalatoborate, lithium dioxalatoborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) salt and lithium hexafluorophosphate.

[0011] The second aspect of the present invention provides a method for preparing a pre-lithiated composite carbon material, comprising the steps of:

[0012] (I) Preparation of Precursor

[0013] Adding a silicon source, a carbon source and a nucleation additive to an alcohol-water mixed solution to obtain an emulsion, and then subjecting the mixture to hydrothermal treatment, filtering and drying to obtain a precursor;

[0014] (II) Etching

[0015] After performing step (1) once or multiple times, the precursor is carbonized, hydrogen fluoride is added to the carbonized product for reaction, and then the product is washed with water and dried to obtain carbon spheres;

[0016] (III) Prelithiation

[0017] After mixing the carbon spheres and lithium powder, heating in vacuum until the lithium powder is vaporized to perform pre-lithiation to obtain pre-lithiated carbon spheres;

[0018] (IV) Coating

[0019] The pre-lithiated carbon spheres and the solid electrolyte are mixed, and vacuum heated until the solid electrolyte melts to cover the pre-lithiated carbon spheres.

[0020] In the preparation method of the present invention, a hydrothermal reaction is carried out by a silicon source, a carbon source and a nucleation additive, that is, a carbon sphere with at least two layers of structure is prepared by a soft template method. Then, by etching with hydrogen fluoride, hydrogen fluoride reacts with SiO2 in the carbon sphere to generate water and water-soluble fluorosilicic acid (H2SiF6), and then the fluorosilicic acid is removed by washing with water and dried to obtain a hollow carbon sphere with one or more cavities. The hollow carbon sphere is reacted with lithium powder, and after the lithium powder is heated to a vaporized state under vacuum protection, the lithium powder is at least physically vapor-deposited into the internal cavity of the hollow carbon sphere due to the capillary conduction effect to form a pre-lithiated carbon sphere. After the solid electrolyte is melted, the surface of the pre-lithiated carbon sphere is coated to form an electrolyte layer. The electrolyte layer is dissolved in the organic solvent of the electrolyte in the subsequent chemical composition process to expose the internal lithium source, thereby achieving lithium replenishment, and the electrolyte layer can act as a protective layer before chemical formation to prevent the lithium powder from leaking or reacting in advance to affect the effect of lithium replenishment. In the preparation method of the present invention, lithium is sealed in the cavity of the hollow carbon sphere to increase the density of the electron path in the contact interface, and the generation of "dead lithium" is significantly reduced during the lithium replenishment process, so a high lithium source utilization rate can be achieved.

[0021] As a technical solution of the present invention, the alcohol-water mixed solution is a mixed solution in which the volume ratio of water to ethanol is 1:5-10.

[0022] As a technical solution of the present invention, the silicon source includes one or more of methyl orthosilicate, ethyl orthosilicate, trimethylchlorosilane, tetramethylsilane, dimethyldichlorosilane, silicon tetrachloride, vinyl silane, aminosilane, methacryloxysilane and tetraethyl orthosilicate.

[0023] As a technical solution of the present invention, the carbon source includes one or more of glacial acetic acid, benzoic acid, oxalic acid, squaric acid, ethylene glycol, glycerol, ethanol, methanol, formaldehyde, hydroquinone and resorcinol.

[0024] As a technical solution of the present invention, the nucleating additive includes ammonia water.

[0025] As a technical solution of the present invention, the ratio of the silicon source, the carbon source and the nucleating additive is 0.30-0.40:0.80-0.90:1.00-3.00:2.00-3.00.

[0026] As a technical solution of the present invention, the silicon source is added in multiple times at room temperature, and each time it is added, it is stirred for a certain period of time before proceeding to the next step.

[0027] As a technical solution of the present invention, the temperature of the hydrothermal treatment is 150-220° C. and the time is 15-48 hours.

[0028] As a technical solution of the present invention, in the preparation of the precursor in step (I), the drying temperature is 50 to 75° C. and the drying time is 8 to 20 hours.

[0029] As a technical solution of the present invention, the carbonization is carried out under an inert atmosphere, and the inert atmosphere includes at least one of nitrogen, helium, argon and neon.

[0030] As a technical solution of the present invention, the carbonization temperature is 800-1300° C., the time is 1-5 hours, and the heating rate is 1-10° C. / min.

[0031] As a technical solution of the present invention, the mass ratio of the carbonized product to the hydrogen fluoride is 1:3-5.

[0032] As a technical solution of the present invention, the drying temperature in the etching step (II) is 50-75° C. and the drying time is 8-20 hours.

[0033] As a technical solution of the present invention, the particle size of the carbon spheres is 300 to 650 nm.

[0034] As a technical solution of the present invention, the specific surface area of ​​the carbon sphere is 700 to 1600 m 2 / g.

[0035] As a technical solution of the present invention, the total volume of the cavity formed in the carbon sphere after etching is 1.5 to 3.5 cm 3 / g.

[0036] As a technical solution of the present invention, the mass ratio of the carbon spheres to the lithium powder is 1:0.9-1.1.

[0037] As a technical solution of the present invention, the temperature of the vacuum heating in step (III) pre-lithiation is 1300-1400°C.

[0038] As a technical solution of the present invention, the molar mass ratio of the pre-lithiated carbon spheres to the solid electrolyte is 95 to 110:1.

[0039] As a technical solution of the present invention, the temperature of the vacuum heating in step (IV) coating is 120-310°C.

[0040] As a technical solution of the present invention, the solid electrolyte is at least one of lithium difluorooxalatoborate, lithium dioxalatoborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) salt and lithium hexafluorophosphate.

[0041] The third aspect of the present invention provides a method for preparing a negative electrode plate, comprising: mixing a negative electrode material, a binder, a conductive agent and a solvent to form a slurry, coating the slurry on a copper foil, and rolling the slurry after drying. The negative electrode material is the aforementioned pre-lithiation composite carbon material or a pre-lithiation composite carbon material prepared by the aforementioned pre-lithiation composite carbon material preparation method.

[0042] As a technical solution of the present invention, the binder includes at least one of styrene-butadiene rubber latex, carboxymethyl cellulose, polyacrylic acid and polyvinyl alcohol, the conductive agent includes at least one of carbon black, conductive graphite, carbon fiber, carbon nanotubes, graphene and conductive paste, and the solvent includes water.

[0043] As a technical solution of the present invention, the ambient humidity is controlled to be below 0.41% during the rolling process, and the compaction density of the electrode sheet after the rolling process is 1.6 to 1.7 g / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a schematic structural diagram of the pre-lithiation composite carbon material of the present invention.

[0045] Figure 2 The figure is a flow chart for preparing the pre-lithiation composite carbon material of the present invention. DETAILED DESCRIPTION

[0046] The pre-lithiation composite carbon material of the present invention can be used as a negative electrode additive in a secondary battery. When it is used in the negative electrode to prepare a negative electrode plate, it can include the steps of: mixing a negative electrode material, a binder, a conductive agent, a negative electrode additive and a solvent to form a slurry, then coating it on a copper foil, and rolling it after drying. When rolling, the ambient humidity is controlled to be below 0.41%, and the compaction density of the plate after rolling is 1.6-1.7g / cm 3 . Control the humidity to avoid premature dissolution of the moisture-sensitive electrolyte layer after moisture. The compaction density of the pole piece after rolling is close to that of the conventional carbon material. The pressure tonnage and gap width of rolling can be performed according to conventional process standards. Among them, the negative electrode material is a pre-lithiation composite carbon material or a mixture of a pre-lithiation composite carbon material and a conventional negative electrode active material (natural graphite, artificial graphite, soft carbon, hard carbon, silicon-carbon material, silicon-oxygen material). The binder includes at least one of styrene-butadiene rubber emulsion, carboxymethyl cellulose, polyacrylic acid and polyvinyl alcohol. The conductive agent includes at least one of carbon black, conductive graphite, carbon fiber, carbon nanotubes, graphene and conductive slurry. The solvent includes water. The pre-lithiation composite carbon material of the present invention can replenish lithium during use, effectively improve the first coulomb efficiency and cycle performance of the battery, and also improve the rate performance.

[0047] like Figure 1As shown, the pre-lithiation composite carbon material 100 includes a carbon matrix 10, lithium powder 30 and an electrolyte layer 50 coating the carbon matrix 10. The carbon matrix 10 may be a carbon ball including one cavity as shown in a, or a carbon ball including two cavities as shown in b, or a carbon ball including three cavities as shown in c, and of course, more cavities may also be included. The multiple cavities are sequentially surrounded from the inside to the outside, and the lithium powder is filled in the cavities. The thickness of the electrolyte layer is 10 to 70 nm, and the electrolyte in the electrolyte layer is at least one of lithium difluoro oxalate borate, lithium dioxalate borate, bistrifluoromethanesulfonyl imide lithium, bisfluorosulfonyl imide lithium salt and lithium hexafluorophosphate, which is soluble in organic solvents, so it can be dissolved in the organic solvent of the electrolyte in the subsequent formation to expose the lithium powder.

[0048] A method for preparing a pre-lithiated composite carbon material, the process of which is as follows Figure 2 As shown, the following steps may be included.

[0049] (I) Preparation of Precursor

[0050] A silicon source, a carbon source and a nucleation additive are added to an alcohol-water mixed solution to obtain an emulsion mixture, which is then hydrothermally treated, filtered and dried to obtain a precursor.

[0051] (II) Etching

[0052] After step (1) is performed once or multiple times, the precursor is carbonized, hydrogen fluoride is added to the carbonized product for reaction, and then the product is washed with water and dried to obtain carbon spheres.

[0053] (III) Prelithiation

[0054] After mixing carbon spheres and lithium powder, heating in vacuum until the lithium powder is vaporized to perform pre-lithiation to obtain pre-lithiated carbon spheres;

[0055] (IV) Coating

[0056] The pre-lithiated carbon spheres and the solid electrolyte are mixed and heated in a vacuum until the solid electrolyte melts to cover the pre-lithiated carbon spheres.

[0057] Wherein, in the preparation of the precursor of step (I), the alcohol-water mixed solution is a mixed solution in which the volume ratio of water to ethanol is 1:5 to 10. As an example, the volume ratio can be but is not limited to 1:5, 1:6, 1:7, 1:8, 1:9, 1:10. The silicon source includes one or more of methyl orthosilicate, ethyl orthosilicate, trimethylchlorosilane, tetramethylsilane, dimethyldichlorosilane, silicon tetrachloride, vinyl silane, aminosilane, methacryloxysilane and tetraethyl orthosilicate. The carbon source includes one or more of glacial acetic acid, benzoic acid, oxalic acid, squaric acid, ethylene glycol, glycerol, ethanol, methanol, formaldehyde, hydroquinone and resorcinol. The nucleating additive includes ammonia water. The mass ratio of silicon source, carbon source and nucleating additive is 0.30-0.40:0.80-0.90:1.00-3.00:2.00-3.00, such as ammonia solution (28wt.%): formaldehyde (RF) (37wt.%): resorcinol: tetraethyl orthosilicate (TEOS) is 0.38:0.84:2.00:2.43. The silicon source is added in multiple times at room temperature, and each time it is added, it is stirred for a certain time before proceeding to the next step. The temperature of the hydrothermal treatment is 150-220°C, and the time is 15-48h. The drying temperature is 50-75°C, and the time is 8-20h. The operation of the precursor in step (I) can be one or more times to form Figure 2 The number of cavities filled with lithium powder is controllable, so a suitable number of cavities can be selected for pre-lithiation according to actual needs, so the pre-lithiation amount can also be controlled.

[0058] In step (II) etching, carbonization is carried out under an inert atmosphere, and the inert atmosphere includes at least one of nitrogen, helium, argon and neon. The carbonization temperature is 800-1300°C, the time is 1-5 hours, and the heating rate is 1-10°C / min. The mass ratio of the carbonized product to hydrogen fluoride is 1:3-5. The drying temperature during etching is 50-75°C, and the time is 8-20 hours. The particle size of the carbon sphere is 300-650nm, and the specific surface area of ​​the carbon sphere is 700-1600m 2 / g, and the total volume of the cavity formed in the carbon sphere after etching is 1.5~3.5cm 3 / g. After etching, the pore volume and specific surface area of ​​the carbon spheres are large, which will be beneficial to the addition and removal of lithium in the subsequent pre-lithiation process.

[0059] In step (III) pre-lithiation, the mass ratio of carbon spheres to lithium powder is 1:0.9-1.1, and further, the mass ratio of carbon spheres to lithium powder is 1:1. The vacuum heating temperature is 1300-1400° C. The lithium powder is at least deposited in the cavity after vaporization.

[0060] In step (IV) coating, the molar mass ratio of the pre-lithiated carbon spheres to the solid electrolyte is 95 to 110:1, and further, the mass ratio of the pre-lithiated carbon spheres to the solid electrolyte is 100:1. The vacuum heating temperature is 120 to 310°C, and the solid electrolyte is at least one of lithium difluorooxalatoborate, lithium dioxalatoborate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide and lithium hexafluorophosphate.

[0061] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0062] Example 1

[0063] This embodiment is Figure 1 The pre-lithiation composite carbon material shown in a includes a carbon matrix, lithium powder and an electrolyte layer covering the carbon matrix. The carbon matrix is ​​a carbon sphere including a cavity, the lithium powder is filled in the cavity, and the electrolyte in the electrolyte layer is lithium difluorooxalate borate. The preparation steps are as follows.

[0064] (I) Preparation of Precursor

[0065] Deionized water and ethanol were mixed in a volume ratio of 1:7 to form a homogeneous solution. Tetraethyl orthosilicate (accounting for 40% of the total mass of tetraethyl orthosilicate), resorcinol, ammonia solution (28wt.%) and formaldehyde solution (37wt.%) (in the reaction, the mass ratio of total tetraethyl orthosilicate, resorcinol, ammonia solution (28wt.%) and formaldehyde solution was 0.38:0.84:2.00:2.43) were added to the above homogeneous solution in sequence to obtain a mixture. The mixture was vigorously stirred at room temperature for 6h, and then 30wt.% of tetraethyl orthosilicate was added and stirred for 24h, and then the remaining tetraethyl orthosilicate was added to obtain an emulsion mixture. The emulsion mixture was hydrothermally treated at 180°C for 24h in a Teflon-lined autoclave. The solid product was collected by vacuum filtration and dried in an oven at 60°C for 12h to obtain a precursor.

[0066] (II) Etching

[0067] The precursor was carbonized at 1000°C in an argon flow tube furnace for 3 hours with a heating rate of 5°C / min. Hydrogen fluoride was added to the carbonized product (the mass ratio of the carbonized product to hydrogen fluoride was 1:3) for reaction, then washed with water and dried in an oven at 70°C for 15 hours to obtain carbon spheres. The particle size of the carbon spheres was 320nm and the specific surface area of ​​the carbon spheres was 726.26m 2 / g, the total volume of the cavity is 1.55cm 3 / g.

[0068] (III) Prelithiation

[0069] After carbon spheres and lithium powder are mixed in a mass ratio of 1:1, they are heated to 1300°C in vacuum. After the lithium powder is vaporized, it is physically vapor-deposited onto the outer surface and interior of the hollow carbon spheres due to the capillary conduction effect. After the pre-lithiation of the carbon spheres is completed, the temperature is rapidly lowered to obtain pre-lithiation multilayer carbon spheres.

[0070] (IV) Coating

[0071] The pre-lithiated carbon spheres were mixed with lithium difluorooxalatoborate at a ratio of 100:1 by molar mass, and the mixture was heated to 270° C. under vacuum. The lithium difluorooxalatoborate melted and completely covered the pre-lithiated carbon spheres, and then the mixture was cooled to room temperature and dispersed to obtain a pre-lithiated composite carbon material.

[0072] Example 2

[0073] This embodiment is Figure 1 The pre-lithiation composite carbon material shown in b includes a carbon matrix, lithium powder and an electrolyte layer covering the carbon matrix. The carbon matrix is ​​a carbon ball including two cavities, the lithium powder is filled in the cavity, and the electrolyte in the electrolyte layer is lithium hexafluorophosphate and lithium dioxalate borate. The preparation steps are as follows.

[0074] (I) Preparation of Precursor

[0075] Deionized water and ethanol were mixed in a volume ratio of 1:5 to form a homogeneous solution. Methyl orthosilicate (accounting for 50% of the total mass of methyl orthosilicate), resorcinol and ammonia solution (30wt.%) (in the reaction, the mass ratio of methyl orthosilicate, resorcinol and ammonia solution (30wt.%) was 2.43:2.00:0.38) were added to the above homogeneous solution in sequence to obtain a mixture. The mixture was vigorously stirred at room temperature for 8h, and then 25wt.% of methyl orthosilicate was added and continued to stir for 20h, and then the remaining methyl orthosilicate was added to obtain an emulsion mixture. The emulsion mixture was hydrothermally treated at 200°C for 30h in a Teflon-lined autoclave. The solid product was collected by vacuum filtration and dried in an oven at 75°C for 15h. The previous operation was repeated once to obtain a precursor.

[0076] (II) Etching

[0077] The precursor was carbonized at 1100°C in a nitrogen flow tube furnace for 4 hours with a heating rate of 8°C / min. Hydrogen fluoride was added to the carbonized product (the mass ratio of the carbonized product to hydrogen fluoride was 1:4). After reaction, the product was washed with water and dried in an oven at 65°C for 20 hours to obtain carbon spheres. The particle size of the carbon spheres was 450nm and the specific surface area of ​​the carbon spheres was 1537.32m 2 / g, the total volume of the cavity is 3.44cm 3 / g.

[0078] (III) Prelithiation

[0079] After mixing carbon spheres and lithium powder in a mass ratio of 1:1.1, they are heated to 1350°C in vacuum. After the lithium powder is vaporized, it is physically vapor-deposited onto the outer surface and interior of the hollow carbon spheres due to the capillary conduction effect. After the pre-lithiation of the carbon spheres is completed, the temperature is rapidly lowered to obtain pre-lithiation multilayer carbon spheres.

[0080] (IV) Coating

[0081] Pre-lithiated carbon spheres, lithium hexafluorophosphate and lithium dioxalatoborate were mixed in a molar ratio of 105:0.8:0.2, and the mixture was heated to 310°C under vacuum. The lithium hexafluorophosphate and lithium dioxalatoborate melted and completely covered the pre-lithiated carbon spheres, and then the mixture was cooled to room temperature and dispersed to obtain a pre-lithiated composite carbon material.

[0082] Example 3

[0083] This embodiment is Figure 1 The pre-lithiation composite carbon material shown in c includes a carbon matrix, lithium powder and an electrolyte layer covering the carbon matrix. The carbon matrix is ​​a carbon ball including three cavities, lithium powder is filled in the cavities, and the electrolyte in the electrolyte layer is lithium difluorooxalate borate. The preparation steps are as follows.

[0084] (I) Preparation of Precursor

[0085] Deionized water and ethanol were mixed in a volume ratio of 1:7 to form a homogeneous solution. Tetraethyl orthosilicate (accounting for 40% of the total mass of tetraethyl orthosilicate), resorcinol, ammonia solution (28wt.%) and formaldehyde solution (37wt.%) (in the reaction, the total ammonia solution (28wt.%): formaldehyde (RF) (37wt.%): resorcinol: tetraethyl orthosilicate (TEOS) active material mass ratio was 0.40:0.85:1.85:2.87) were added to the above homogeneous solution in sequence to obtain a mixture. The mixture was vigorously stirred at room temperature for 6h, and then 30wt.% of tetraethyl orthosilicate was added and stirred for 24h, and then the remaining tetraethyl orthosilicate was added to obtain an emulsion mixture. The emulsion mixture was hydrothermally treated at 180°C for 24h in a Teflon-lined autoclave. The solid product was collected by vacuum filtration and dried in an oven at 60°C for 12h to obtain a precursor. The previous operation was repeated twice to obtain a precursor.

[0086] (II) Etching

[0087] The precursor was carbonized at 1000°C in an argon flow tube furnace for 3 hours with a heating rate of 5°C / min. Hydrogen fluoride was added to the carbonized product (the mass ratio of the carbonized product to hydrogen fluoride was 1:5) for reaction, then washed with water and dried in an oven at 70°C for 15 hours to obtain carbon spheres. The particle size of the carbon spheres was 580nm and the specific surface area of ​​the carbon spheres was 1594.28m 2 / g, the total volume of the cavity is 3.10cm 3 / g.

[0088] (III) Prelithiation

[0089] After carbon spheres and lithium powder are mixed in a mass ratio of 1:1, they are heated to 1300°C in vacuum. After the lithium powder is vaporized, it is physically vapor-deposited onto the outer surface and interior of the hollow carbon spheres due to the capillary conduction effect. After the pre-lithiation of the carbon spheres is completed, the temperature is rapidly lowered to obtain pre-lithiation multilayer carbon spheres.

[0090] (IV) Coating

[0091] The pre-lithiated carbon spheres were mixed with lithium difluorooxalatoborate at a ratio of 100:1 by molar mass, and the mixture was heated to 270° C. under vacuum. The lithium difluorooxalatoborate melted and completely covered the pre-lithiated carbon spheres, and then the mixture was cooled to room temperature and dispersed to obtain a pre-lithiated composite carbon material.

[0092] Comparative Example 1

[0093] The pre-lithiation composite carbon material of this comparative example comprises a carbon matrix and lithium powder. The carbon matrix is ​​a carbon ball including a cavity, and the lithium powder is filled in the cavity. The preparation steps are as follows.

[0094] (I) Preparation of Precursor

[0095] Deionized water and ethanol were mixed in a volume ratio of 1:7 to form a homogeneous solution. Tetraethyl orthosilicate (accounting for 40% of the total mass of tetraethyl orthosilicate), resorcinol, ammonia solution (28wt.%) and formaldehyde solution (37wt.%) (in the reaction, the mass ratio of ammonia solution (28wt.%): formaldehyde (RF) (37wt.%): resorcinol: tetraethyl orthosilicate (TEOS) active substances was 0.38:0.84:4.00:4.85) was added to the above homogeneous solution to obtain a mixture. The mixture was vigorously stirred at room temperature for 6h, and then 30wt.% of tetraethyl orthosilicate was added and stirred for 24h, and then the remaining tetraethyl orthosilicate was added to obtain an emulsion mixture. The emulsion mixture was hydrothermally treated at 180°C for 24h in a Teflon-lined autoclave. The solid product was collected by vacuum filtration and dried in an oven at 60°C for 12h to obtain a precursor.

[0096] (II) Etching

[0097] The precursor was carbonized at 1000°C in an argon flow tube furnace for 3 hours with a heating rate of 5°C / min. Hydrogen fluoride was added to the carbonized product (the mass ratio of the carbonized product to hydrogen fluoride was 1:5) for reaction, then washed with water and dried in an oven at 70°C for 15 hours to obtain carbon spheres. The particle size of the carbon spheres was 320nm and the specific surface area of ​​the carbon spheres was 726.26m 2 / g, the total volume of the cavity is 1.55cm 3 / g.

[0098] (III) Prelithiation

[0099] The carbon spheres and lithium powder are mixed in a mass ratio of 1:1 and heated to 1300°C in vacuum. The lithium powder is vaporized and physically vapor deposited onto the outer surface and interior of the hollow carbon spheres due to the capillary conduction effect. After the carbon spheres are pre-lithiated, the temperature is rapidly lowered to obtain a pre-lithiated composite carbon material.

[0100] The pre-lithiation composite carbon materials prepared in Examples 1 to 3 and Comparative Example 1 were used as negative electrode additives to prepare negative electrode sheets 1 to 4. The preparation process of the negative electrode sheet includes mixing artificial graphite, pre-lithiation composite carbon material, styrene-butadiene rubber latex, carboxymethyl cellulose and conductive graphite in water at a mass ratio of 95.2:0.8:1.8:1.2:1 to form a slurry, then coating it on a copper foil, and then drying it to control the ambient humidity to be below 0.41% for rolling. After rolling, the compaction density of the sheet is 1.6 g / cm 3 .

[0101] In addition, artificial graphite, styrene-butadiene rubber latex, carboxymethyl cellulose and conductive graphite were mixed in water at a mass ratio of 95.2:2.3:1.7:1 to form a slurry, which was then coated on a copper foil. After drying, the ambient humidity was controlled to be below 0.41% and rolled to obtain a negative electrode sheet 5. The compaction density of the sheet after rolling was 1.6 g / cm 3 .

[0102] Negative pole pieces 1 to 4 were used, metal lithium sheets were used as counter electrodes, 1 mol / L LiPF6 and a three-component mixed solvent of EC:DMC:EMC=1:1:1 (v / v / v) were mixed to form an electrolyte, a polypropylene microporous membrane was used as a separator, and button cells 1 to 4 were assembled in a glove box filled with inert gas. In addition, negative pole piece 5 was used, metal lithium sheets were used as counter electrodes, 1 mol / L LiPF6 and a three-component mixed solvent of EC:DMC:EMC=1:1:1 (v / v / v) were mixed to form an electrolyte, a polypropylene microporous membrane was used as a separator, and a lithium sheet was placed between the negative pole piece 5 and the separator, and button cell 5 was assembled in a glove box filled with inert gas. Charge and discharge tests were performed on button cells 1 to 5 on a battery test system, and the results are shown in Table 1.

[0103] The first charge and discharge performance test: At room temperature, discharge at a constant current of 0.1C until the voltage reaches 0.01V, then discharge at a constant current of 0.02C until the voltage reaches 0.005V, and charge at a constant current of 0.1C until the voltage reaches 1.5V to obtain the first coulombic efficiency.

[0104] Rate performance test: Under room temperature conditions, cycle at a current of 0.1C for 5 weeks, then cycle at a current of 0.2C for 5 weeks, 0.5C for 5 weeks, 1.0C for 5 weeks, 2.0C for 5 weeks, and finally cycle at a current of 0.1C for 5 weeks.

[0105] Cyclic performance test: Under normal temperature conditions, 0.5C constant current charge and discharge to 0.01V, then 0.05C constant current discharge to 0.005V, and finally 0.5C constant current charge to 1.5V to obtain the de-lithiation specific capacity. This cycle is repeated 300 times, and the capacity retention rate after 300 cycles is calculated. The 300-week capacity retention rate is the ratio of the de-lithiation specific capacity in the 300th week to the de-lithiation specific capacity in the first week.

[0106] Table 1 Electrochemical performance test results of button cells 1 to 5

[0107]

[0108] From the results in Table 1, it can be seen that the present invention adopts a soft template method combined with hydrofluoric acid etching to prepare carbon spheres with a plurality of cavities. The deposition of lithium powder in the cavity and the coating of the outer electrolyte layer can make the prepared pre-lithiation composite carbon material be used for lithium supplementation, effectively improving the first coulombic efficiency, cycle performance and rate performance of the battery.

[0109] The pre-lithiation composite carbon material of button cell 4 is not coated with an electrolyte layer. The lithium powder in the pre-lithiation composite carbon material may leak or react prematurely before formation activation, thus affecting the lithium replenishment effect. Therefore, the first coulombic efficiency, cycle performance and rate performance are not good.

[0110] The button cell 5 directly uses lithium sheets, and the lithium source utilization rate is reduced in the later stage of the cycle, resulting in a decrease in the cycle performance.

[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A pre-lithiation composite carbon material, characterized in that: It includes a carbon matrix, lithium powder and an electrolyte layer covering the carbon matrix. The carbon matrix is ​​a carbon ball including a plurality of cavities. The plurality of cavities are sequentially arranged from the inside to the outside. The lithium powder is filled in the cavities. The electrolyte layer is soluble in an organic solvent.

2. The pre-lithiation composite carbon material according to claim 1, characterized in that The number of the cavities is 1 to 3.

3. The pre-lithiation composite carbon material according to claim 1, characterized in that: The thickness of the electrolyte layer is 10-70 nm.

4. The pre-lithiation composite carbon material according to claim 1, characterized in that: The electrolyte in the electrolyte layer is at least one of lithium difluorooxalatoborate, lithium dioxalatoborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) salt and lithium hexafluorophosphate.

5. A method for preparing a pre-lithiation composite carbon material, characterized in that: Includes steps: (I) Preparation of Precursor Adding a silicon source, a carbon source and a nucleation additive to an alcohol-water mixed solution to obtain an emulsion, and then subjecting the mixture to hydrothermal treatment, filtering and drying to obtain a precursor; (II) Etching After performing step (1) once or multiple times, the precursor is carbonized, hydrogen fluoride is added to the carbonized product for reaction, and then the product is washed with water and dried to obtain carbon spheres; (III) Prelithiation After mixing the carbon spheres and lithium powder, heating in vacuum until the lithium powder is vaporized to perform pre-lithiation to obtain pre-lithiated carbon spheres; (IV) Coating The pre-lithiated carbon spheres and the solid electrolyte are mixed, and vacuum heated until the solid electrolyte melts to cover the pre-lithiated carbon spheres.

6. The method for preparing a pre-lithiation composite carbon material according to claim 5, characterized in that: The invention comprises at least one of the following features (1) to (20): (1) The alcohol-water mixed solution is a mixed solution in which the volume ratio of water to ethanol is 1:5-10; (2) The silicon source includes one or more of methyl orthosilicate, ethyl orthosilicate, trimethylchlorosilane, tetramethylsilane, dimethyldichlorosilane, silicon tetrachloride, vinyl silane, aminosilane, methacryloxysilane and tetraethyl orthosilicate; (3) The carbon source includes one or more of glacial acetic acid, benzoic acid, oxalic acid, squaric acid, ethylene glycol, glycerol, ethanol, methanol, formaldehyde, hydroquinone and resorcinol; (4) The nucleating additive includes ammonia; (5) The mass ratio of the silicon source, the carbon source and the nucleating additive is 0.30-0.40:0.80-0.90:1.00-3.00:2.00-3.00; (6) The silicon source is added in multiple times at room temperature, and stirred for a certain period of time after each addition before proceeding to the next step; (7) The temperature of the hydrothermal treatment is 150 to 220° C. and the time is 15 to 48 hours; (8) In the preparation of the precursor in step (I), the drying temperature is 50 to 75° C. and the drying time is 8 to 20 hours; (9) The carbonization is carried out under an inert atmosphere, wherein the inert atmosphere comprises at least one of nitrogen, helium, argon and neon; (10) The carbonization temperature is 800-1300° C., the time is 1-5 hours, and the heating rate is 1-10° C. / min; (11) The mass ratio of the carbonized product to the hydrogen fluoride is 1:3-5; (12) The drying temperature in step (II) etching is 50 to 75° C. and the drying time is 8 to 20 hours; (13) The particle size of the carbon spheres is 300 to 650 nm; (14) The specific surface area of ​​the carbon sphere is 700 to 1600 m 2 / g; (15) The total volume of the cavity formed in the carbon sphere after etching is 1.5 to 3.5 cm 3 / g; (16) The mass ratio of the carbon spheres to the lithium powder is 1:0.9-1.1; (17) The temperature of the vacuum heating in the pre-lithiation step (III) is 1300-1400° C.; (18) The molar mass ratio of the pre-lithiated carbon spheres to the solid electrolyte is 95 to 110:1; (19) The vacuum heating temperature in step (IV) is 120 to 310° C.; (20) The solid electrolyte is at least one of lithium difluorooxalatoborate, lithium dioxalatoborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) salt and lithium hexafluorophosphate.

7. A method for preparing a negative electrode sheet, characterized in that: include: A negative electrode material, a binder, a conductive agent and a solvent are mixed to form a slurry, which is then coated on a copper foil and rolled after drying. The negative electrode material is a pre-lithiation composite carbon material as described in any one of claims 1 to 4 or a pre-lithiation composite carbon material prepared by the method for preparing a pre-lithiation composite carbon material as described in any one of claims 5 to 6.

8. The method for preparing a negative electrode sheet according to claim 7, characterized in that: The binder includes at least one of styrene-butadiene rubber latex, carboxymethyl cellulose, polyacrylic acid and polyvinyl alcohol, the conductive agent includes at least one of carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene and conductive paste, and the solvent includes water.

9. The method for preparing a negative electrode sheet according to claim 7, characterized in that: The ambient humidity is controlled to be below 0.41% during the rolling process, and the compaction density of the electrode sheet after the rolling process is 1.6-1.7 g / cm 3 .

10. A secondary battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material is the pre-lithiation composite carbon material described in any one of claims 1 to 4 or the pre-lithiation composite carbon material prepared by the method for preparing the pre-lithiation composite carbon material described in any one of claims 5 to 6.

Citation Information

Patent Citations

  • Preparation method for multi-layer carbon hollow sphere anode material

    CN104319402A

  • Hard carbon composite material, as well as preparation method and application thereof

    CN113422052A

  • Internal lithium-loving type multiple confinement / induction lithium negative electrode and preparation method and application thereof

    CN113540402A

  • Coated positive electrode active material for lithium ion secondary battery, and manufacturing and evaluation methods thereof

    JP2019140091A